Relationship between immediate post-operative appearance and 6-week operative outcome in trichiasis surgery. - Shannath L Merbs; Jennifer C Harding; Sandra D Cassard; Beatriz E Munoz; Sheila K West; Emily W Gower (Public Library of Science (PLoS), 2012)
BACKGROUND: Surgical technique, including suture placement and tension, is believed to contribute to the outcome of bilamellar tarsal rotation surgery for trachomatous trichiasis. However, the immediate post-operative appearance that minimizes the chance of recurrence and other adverse outcomes has not been investigated. METHODOLOGY/PRINCIPAL FINDINGS: To explore whether the degree of correction immediately after surgery is predictive of surgical outcome at the 6-week post-operative visit, photographs taken immediately after surgery were used to predict surgical outcomes, including the severity of eyelid contour abnormality and trichiasis recurrence. Both eyelid contour abnormalities and recurrence were accurately predicted from the immediate post-operative photographs by an experienced oculoplastic surgeon 85% and 70% of the time, respectively. Participants with a "slight over-correction" that resulted in no eyelid contour abnormality and no recurrence were used to identify immediate post-operative contours that lead to a successful surgical outcome. CONCLUSIONS/SIGNIFICANCE: The immediate post-operative eyelid contour is an important indicator of post-operative success of BLTR surgery. Based upon our findings, we developed a Surgery Photocard. This card illustrates some examples of immediate post-surgical appearances, which led to a successful outcome, as well as sub-optimal appearances, which led to poor surgical outcomes. The card also provides suggestions for improving the appearance by adjusting the suture placement or tension based upon standard oculoplastic principles.